'It's a Family Responsibility': Family and Cultural Connection for Aboriginal Children in Kinship Care. (29th October 2014) - Kiraly, Meredith; James, Julieanne; Humphreys, Cathy
<x content-type="archive" xml:space="preserve">Abstract</x> Kinship care as a form of protective care in Australia has grown considerably over the past decade. The University of Melbourne Family Links: Kinship Care and Family Contact research project comprised a survey of kinship carers and consultations with key stakeholders. Given the significant over-representation of Indigenous children in kinship care arrangements, the project included a nested study of Indigenous kinship care. Research participants stressed the imperative for Indigenous children to be connected to family, community and culture. However, survey responses indicated that in many cases, family and cultural connections were not being assisted by cultural support planning. Indigenous caseworkers described the complexities of facilitating family contact, highlighting good practice as well as dilemmas and shortcomings in culturally sensitive practice. There was much evidence of the straitened circumstances of Indigenous kinship carers and unmet support needs among carers, both Indigenous and non-Indigenous. Suggestions are made about ways in which children in kinship care might be better supported to maintain their family relationships.